2021
DOI: 10.1039/d0nh00674b
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis/pyroptosis dual-inductive combinational anti-cancer therapy achieved by transferrin decorated nanoMOF

Abstract: Non-apoptotic cell death such as ferroptosis and pyroptosis has shed new light on cancer treatment, while whose combinational therapy has not been fully explored yet. Herein, a dual-inductive nano-system to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 25 publications
0
59
0
Order By: Relevance
“…The typical pyroptotic pathway is sparked by the activation of nucleotide-binding domain leucine-rich repeats family protein 3 (NLRP3) inflammasomes as well as the associated inflammatory response [13,14]. Several reports have verified that pyroptosis plays a critical role in tumorigenesis and cancer treatment [15][16][17][18][19]. Notably, various cancers, including colon cancer [20,21], gastric cancer [22], hepatocellular carcinoma [23,24], breast cancer [25,26] and lung cancer [27,28], are sensitive to pyroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The typical pyroptotic pathway is sparked by the activation of nucleotide-binding domain leucine-rich repeats family protein 3 (NLRP3) inflammasomes as well as the associated inflammatory response [13,14]. Several reports have verified that pyroptosis plays a critical role in tumorigenesis and cancer treatment [15][16][17][18][19]. Notably, various cancers, including colon cancer [20,21], gastric cancer [22], hepatocellular carcinoma [23,24], breast cancer [25,26] and lung cancer [27,28], are sensitive to pyroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the concomitant methylene blue release induced fluorescence recovery, endowing the nanomaterials with multimodal imaging-guided PDT/FBT. In another example, Fe 3+ -containing MOFs loaded with piperlongumine (a FIN) were coated with a transferrin-decorated pH sensitive lipid layer to form the nanodrug ( Xu, R. et al, 2021 ). Crucially, after treatment with this nanoagent, the cellular iron concentration increased dramatically due to the iron-containing MOF, and piperlongumine strengthened the ferroptosis via providing H 2 O 2 for the dual induction system.…”
Section: Nanomaterials As Finsmentioning
confidence: 99%
“…Xu et al recently reported NPs inducing FERR decorated with TS (Table 2) [45]. The NPs were loaded with piperlongumine (FERR inducer, Figure 3) and covered with pH sensitive lipid membranes embedding TS (Tf-LipoMof@PL).…”
Section: Nanoparticles For Tumor Targetingmentioning
confidence: 99%